Kampanye Sosial Red Readerhood 2019 Untuk Meningkatkan Minat Baca Anak - Sari, Diah Kencana (Master of Management Diponegoro University, 2019)
Big Bad Wolf Book Sale was first held in Kuala Lumpur, Malaysia, in 2009. seven years later, The Ministry of Culture and Education worked together with PT Jaya Ritel Indonesia to hold Big Bad Wolf Book Sale in Jakarta. Putting forward its vision and mission which is